Sustainable Development Goals (SDGs) Instrumentalization and Neoliberal Hegemony: A Village Perspective - Anggraini, Nefa Wahyuning (Jurnal Pemikiran Sosiologi, 2024)
The implementation of the Sustainable Development Goals (SDGs) for Villages in Indonesia since 2021 marks a significant change in the paradigm of village development. This policy is claimed to be an effort to accelerate sustainable development, but in practice, it constructs villages as objects of state control within the global development architecture. This research aims to examine how the Village SDGs operate within the power relations of the state, market, and village, and to evaluate their implications for the village's autonomy in determining its development direction. Using the Socio-Institutional Neoliberalism (SIN) approach by Toby Carroll, this research examines how village development policies are reproduced within the framework of global economic-political interests. This research uses qualitative methods with case studies in the Panggungharjo Village and Pandowoharjo Village, Yogyakarta. Data were collected through observation, in-depth interviews, and policy document analysis, and then analyzed using Yin's pattern matching technique. The research results indicate that the implementation of the Village SDGs is more oriented towards administration and compliance with global indicators rather than substantial village empowerment. The digitalization of village development not only complicates bureaucracy but also increases the village's dependence on central regulations, widens the technology access gap, and strengthens state and market control over the village. This research recommends a more democratic and participatory village development approach, allowing villages to implement development based on their local conditions. The reformulation of the Village SDGs policy must be oriented towards village independence, not merely administrative compliance with global targets.